The integration of goats in the livestock systems of the arid and semi-arid Africa - Wilson, R.T. (Departmento de Difusao de Tecnologia, 1987)
Outlines the importance of goats in arid & semi-arid Africa and describes the farming systems in which they are present. Discusses the value of goats in the context of the percentage of families owning them and the numbers of goats per family and in relation to other stock. Examines resource utilization by goats & other domestic herbivores, and their contribution to human welfare, and their economic value.